IJCM_357A: Smartphone addiction and physical activity among students of a Medical College in Bengaluru-a cross-sectional study - Dinesh Indu; Ravish K S; Ranganath T S (Indian Journal of Community Medicine, 2024)
Background: Smartphones have become an indispensable necessity for medical students because of their various demands and comforts. The excessive use of smartphones may lead to addiction which can negatively affect physical and mental health including physical activity. The relationship between smartphone addiction and physical activity needs exploration. Hence this study was undertaken to assess the magnitude of smartphone addiction and to explore its association with physical activity among students of a medical college in Bengaluru. Objective: To assess smartphone addiction and its association with physical activity among students of a medical college in Bengaluru. Methodology: A cross-sectional study was conducted among students of Bangalore Medical College and Research Institute. Based on a study done in Maharashtra(p=46.15%), the sample size was calculated as 382. Study subjects were recruited by stratified random sampling and probability-proportional to size sampling was used to select study participants across various strata. Data was collected using a pretested semi-structured questionnaire. Smartphone addiction was assessed by smartphone addiction scale-short version (SAS-SV) and physical activity by international physical activity questionnaire-short form (IPAQ-SF). The data collected was entered in MS Excel and analyzed using SPSS 21.0. Results: Among 382 students 164(43%) were found to have smartphone addiction. The primary use of smartphones was for social networking. Physical activity, duration of smartphone usage, and use of the smartphone right before sleeping were associated significantly with smartphone addiction. Conclusion: The problem of smartphone addiction has reached an alarming level. There is a need to create awareness about the problem and plan effective strategies to address it.